Efficacy and safety of methylene blue in patients with vasodilatory shock: A systematic review and meta-analysis - Zhao, Cong-Cong; Zhai, Yu-Jia; Hu, Zhen-Jie; Huo, Yan; Li, Zhi-Qiang; Zhu, Gui-Jun (Frontiers in Medicine, 2022)
Background: The role of methylene blue (MB) in patients with vasodilatory shock is unclear. The purpose of this systematic review and meta-analysis was to evaluate the efficacy and safety of MB in patients with vasodilatory shock. Methods: We searched MEDLINE at PubMed, Embase, Web of Science, Cochrane, CNKI, CBM and Wanfang Medical databases for all observational and intervention studies comparing the effect of MB vs. control in vasodilatory shock patients. This study was performed in accordance with the PRISMA statement. There were no language restrictions for inclusion. Results: A total of 15 studies with 832 patients were included. Pooled data demonstrated that administration of MB along with vasopressors significantly reduced mortality (odds ratio (OR) 0.54, 95% confidence interval (CI) 0.34 to 0.85, P = 0.008; I2 = 7%). This benefit in mortality rate was also seen in a subgroup analysis including randomized controlled trials and quasi-randomized controlled trials. Moreover, subgroup analyses found a significant difference in mortality between groups, favoring continuous infusion MB in septic shock patients. In addition, the vasopressor requirement was reduced in the MB group (mean difference (MD) -0.77, 95%CI -1.26 to -0.28, P = 0.002; I2 = 80%). Regarding hemodynamics, MB increased the mean arterial pressure, heart rate and peripheral vascular resistance. In respect to organ function, MB was associated with a lower incidence of renal failure, while in regards to oxygen metabolism, it was linked to reduced lactate levels. MB had no effect on the other outcomes and no serious side effects. Conclusions: Concomitant administration of MB and vasopressors improved hemodynamics, decreased vasopressor requirements, reduced lactate levels, and improved survival in patients with vasodilatory shock. However, further studies are required to confirm these findings.